Associated conditions in small fiber neuropathy – a large cohort study and review of the literature. (18th December 2017) - de Greef, B. T. A.; Hoeijmakers, J. G. J.; Gorissen‐Brouwers, C. M. L.; Geerts, M.; Faber, C. G.; Merkies, I. S. J.
Abstract : Background and purpose: Small fiber neuropathy (SFN) is a common disorder leading to neuropathic pain and autonomic symptoms. The objective of this study was to investigate associated conditions in a large cohort of SFN patients and compare the prevalence to healthy individuals. Methods: A total of 921 patients with pure SFN were screened according to a standardized comprehensive diagnostic algorithm and compared with literature findings. Results: No associated condition could be found in 53% of the patients. Autoimmune diseases, sodium channel gene mutations, diabetes mellitus including glucose intolerance, and vitamin B12 deficiencies were more prevalent than reported literature findings, followed by alcohol abuse, chemotherapy, monoclonal gammopathy of undetermined significance, and haemochromatosis. In patients who were already known with a possible underlying condition at screening, additional underlying conditions were still found in another 26.7% of patients. Conclusions: Based on these results, it is recommended that patients with pure SFN are screened at least for autoimmune diseases, sodium channel gene mutations, diabetes mellitus including glucose intolerance, and vitamin B12 deficiency, even when they already have a potential underlying condition at referral.